Half-Sandwich Ru(II) Halogenido, Valproato and 4-Phenylbutyrato Complexes Containing 2,2'-Dipyridylamine: Synthesis, Characterization, Solution Chemistry and In Vitro Cytotoxicity - Štarha, Pavel; Trávníček, Zdeněk; Křikavová, Radka; Dvořák, Zdeněk (Molecules, 2016)
Halogenido and carboxylato Ru(II) half-sandwich complexes of the general composition [Ru(η⁶-p-cym)(dpa)X]PF₆ (1-5) were prepared and thoroughly characterized with various techniques (e.g., mass spectrometry, NMR spectroscopy and X-ray analysis); dpa = 2,2'-dipyridylamine; p-cym = p-cymene; X = Cl(-) (for 1), Br(-) (for 2), I(-) (for 3), valproate(1-) (for 4) or 4-phenylbutyrate(1-) (for 5). A single-crystal X-ray analysis showed a pseudo-octahedral piano-stool geometry of [Ru(η⁶-p-cym)(dpa)I]PF₆ (3), with a η⁶-coordinated p-cymene, bidentate N-donor dpa ligand and iodido ligand coordinated to the Ru(II) atom. The results of the ¹H-NMR solution behaviour studies proved that the complexes 1-5 hydrolyse were in the mixture of solvents used (10% MeOD-d₄/90% D₂O). Complexes 1-5 were in vitro inactive against the A2780 human ovarian carcinoma cell line, up to the highest tested concentration (IC50 > 100 μM).
Keywords: glutathion; Cell Line, Tumor; nádory; Glutathione; Crystallography, X-Ray; Antineoplastic Agents; Humans; molekulární modely; Neoplasms; Solvents; protinádorové látky; racionální návrh léčiv; Drug Design; protonová magnetická rezonanční spektroskopie; Ruthenium; Models, Molecular; Molecular Structure; krystalografie rentgenová; Proton Magnetic Resonance Spectroscopy; molekulární struktura; ruthenium; lidé; rozpouštědla; nádorové buněčné linie